2022
DOI: 10.1186/s43042-022-00364-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic evaluation of primary amenorrhea: a study of 100 cases at tertiary centre

Abstract: Background Amenorrhea is the absence of menstruation in women of reproductive age. The physiology of menstruation and reproduction has a strong correlation with the expression of the X chromosome. Early referral for cytogenetic evaluation is recommended for the identification of underlying chromosomal aberrations in amenorrhoea patients. This study aims to estimate the frequency and types of chromosomal abnormalities in primary amenorrhoea (PA) patients in western India and correlate their horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…13.3% of patients evaluated with primary amenorrhea had an abnormal karyotype. Previous studies have reported that 12%–42% of patients with primary amenorrhea have abnormal karyotypes, and this may be due to differences in the selection criteria of the patients 13 . Primary amenorrhea can arise from endocrine disorders, structural and environmental factors, and genetics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13.3% of patients evaluated with primary amenorrhea had an abnormal karyotype. Previous studies have reported that 12%–42% of patients with primary amenorrhea have abnormal karyotypes, and this may be due to differences in the selection criteria of the patients 13 . Primary amenorrhea can arise from endocrine disorders, structural and environmental factors, and genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that 12%–42% of patients with primary amenorrhea have abnormal karyotypes, and this may be due to differences in the selection criteria of the patients. 13 Primary amenorrhea can arise from endocrine disorders, structural and environmental factors, and genetics. When exploring its genetic etiology, cytogenetic abnormalities, should not be neglected as a primary investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic factors are important, as seen in Turner syndrome, marked by a missing or incomplete X chromosome, and Androgen Insensitivity Syndrome (AIS), where individuals with XY chromosomes show reduced or absent response to androgens [ 3 , 4 , 5 ]. Furthermore, different chromosomal abnormalities could also play a role in primary amenorrhea, underscoring the intricate relationship between genetics and reproductive health [ 6 , 7 , 8 ]. Structural abnormalities of the reproductive tract that affect normal menstruation are also a significant factor due to anatomical causes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%